Community Participation in the Implementation of Policy to Prevent and Reduce the Positive Rate of Covid 19 in the Period New Adaptation (New Normal) in the City of Padang in 2021 - Irfan, Asep; Darwel; Suksmerri (proceedinginternational, 2023)
The low level of community participation in preventing and decreasing the positive rate for COVID-19 since this disease only appeared in the city of Padang in early March 2020 until the new adaptation period (new normal) people's ignorant attitude, unwilling to maintain social distancing, physical distancing, lazy To do hand washing with soap or not wanting to wear a mask is an unsolved problem at this time in the city of Padang. This study uses a descriptive method which was conducted in March – November 2021 in the city of Padang. The sampling technique used purposive sampling technique so that the number of samples in this study was 60 respondents. The results showed that 55.8% of respondents avoided shaking hands, respondents' opinions about the effectiveness of running procedures to avoid crowds were 56.3% and respondents' opinions about the reasons people did not comply in carrying out health care programs were mostly the price of masks, face shields, hand sanitizers or PPE. Others tend to be expensive, which is 66.7%. While the responses of respondents to the community infected with Covid 19 were mostly close people, neighbors and their environment providing support, namely 86.7%. It is hoped that the government, both at the city and regional levels, can increase public participation in health protocols through education in community action movements to break the COVID-19 chain.